1992
DOI: 10.1002/art.1780350603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food on the bioavailability of low‐dose methotrexate in patients with rheumatoid arthritis

Abstract: Objective. To evaluate the influence of food on the bioavailability of an oral dose of methotrexate in patients with rheumatoid arthritis.Methods. Methotrexate (15 mg) was given intravenously and orally, with or without a meal, to 10 patients. Blood samples were drawn at specific intervals to evaluate drug levels.Results. Food reduced the peak concentration, from a mean of 0.71 pmoleshiter to 0.49 pmoles/liter (P < 0.02), and slightly increased the time to peak concentration, from a mean of 1.3 hours to 2.0 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 11 publications
4
57
1
3
Order By: Relevance
“…In the treatment of rheumatoid arthritis, the usual dose of methotrexate is in the range of 15 to 17.5 mg/week, although early studies utilized much lower doses and others have reported using higher doses. At the doses commonly used for the treatment of rheumatoid arthritis, the bioavailability of oral methotrexate varies considerably between individuals, but in general is in the range of 70%, and food does not significantly affect uptake of the drug (Fossa et al, 1988;Kozloski et al, 1992;Oguey et al, 1992;Jundt et al, 1993;Lebbe et al, 1994;Bannwarth et al, 1996). There is some evidence that at higher doses oral bioavailability declines, a phenomenon most likely due to the fact that uptake of methotrexate from the gastrointestinal tract is mediated by a saturable transporter, reduced folate carrier 1 ( RFC1 1 ) (Matherly and Goldman, 2003).…”
Section: A Pharmacology Of Low-dose Methotrexatementioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of rheumatoid arthritis, the usual dose of methotrexate is in the range of 15 to 17.5 mg/week, although early studies utilized much lower doses and others have reported using higher doses. At the doses commonly used for the treatment of rheumatoid arthritis, the bioavailability of oral methotrexate varies considerably between individuals, but in general is in the range of 70%, and food does not significantly affect uptake of the drug (Fossa et al, 1988;Kozloski et al, 1992;Oguey et al, 1992;Jundt et al, 1993;Lebbe et al, 1994;Bannwarth et al, 1996). There is some evidence that at higher doses oral bioavailability declines, a phenomenon most likely due to the fact that uptake of methotrexate from the gastrointestinal tract is mediated by a saturable transporter, reduced folate carrier 1 ( RFC1 1 ) (Matherly and Goldman, 2003).…”
Section: A Pharmacology Of Low-dose Methotrexatementioning
confidence: 99%
“…Both methotrexate and 7-hydroxymethotrexate are primarily excreted in the urine, although there is some biliary excretion. The half-life of methotrexate in the serum is in the range of 6 to 8 h after administration of the drug and is undetectable in the serum by 24 h (Fossa et al, 1988;Kozloski et al, 1992;Oguey et al, 1992;Jundt et al, 1993;Lebbe et al, 1994;Bannwarth et al, 1996). By decreasing glomerular filtration rate, nonsteroidal antiinflammatory drugs may increase the time required to eliminate methotrexate, although this interaction is of little clinical significance (Furst, 1995).…”
Section: A Pharmacology Of Low-dose Methotrexatementioning
confidence: 99%
“…However, much higher concentrations (the average maximum concentration is 700 nM) can be achieved temporarily after an oral dose of 15 mg (30,31). The serum concentration quickly drops from 700 to Ͻ100 nM within 12 h and then reaches 1 nM ϳ40 h after administration of the medication (30).…”
Section: Effect Of Ards On Human Peripheral Blood T Cellsmentioning
confidence: 99%
“…13 Pinkerton et al 17 have shown that oral absorption of MTX can be substantially reduced by food; however, there are at least two studies which have demonstrated that bioavailability of the drug is largely independent of food intake. 18,19 To our knowledge, the effect of intestinal disease on MTX absorption has not been previously investigated, therefore, the main purpose of our study was to examine a possible impairment in the absorption of MTX in patients with IBD. We did not perform a complete bioavailability study for 24 h, but, since all patients had normal liver and kidney functions, we may assume that the bioavailability of MTX in all the patient groups was similar.…”
Section: Discussionmentioning
confidence: 99%